SUBSTITUTED PYRIMIDIN-4(3H)-ONES FOR USE IN TREATING CANCER - SINKEVICIUS, Kerstin; WADE, Anna; WOOD, Lauren; DAMBKOWSKI, Carl; LIM, Justin; WALLACE, Eli; VAN VEENHUYZEN, David; WEN, Susanna; BELTRAN, Pedro (2024)
The present disclosure provides a method of treating cancer or a solid tumor (e.g., an advanced or metastatic solid tumor) in a subject with a therapeutically effective amount of a compound of formula (I) or a pharmaceutically acceptable salt, hydrate, solvate, stereoisomer, conformational isomer, tautomer, or a combination thereof, where the subject has one or more mutations in the MAPK pathway and/or one or more mutations in